Short interfering RNA therapeutics: nanocarriers, prospects and limitations. Issue 6 (1st December 2015) - Mehrotra, Neha; Tripathi, Ravi Mani
Abstract : Since the first experiment depicting gene inhibition using RNA interference mechanism, extensive research has been carried out to design targeted delivery systems that use short interfering RNAs (siRNAs) for gene expression regulation. Although several siRNAs loaded nanoparticle systems have reached clinical trial stage, cellular uptake, reticuloendothelial entrapment and endosomal escape still limit the efficacy of these drugs considerably. This review discusses about the RNA interference mechanism, nanostructures being used as non‐viral vectors for targeted delivery, limitations of the common delivery systems and the current siRNA‐loaded nanoparticle formulations undergoing clinical testing.